2021
DOI: 10.28982/josam.922882
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 6 weeks home rehabilitation program for non-ventilated COVID-19 patients after discharge: A case report

Abstract: COVID-19 disease is a pandemic that affects the cardio-respiratory system and causes other systemic problems. The effect of pulmonary rehabilitation (PR) programs for COVID-19 disease sequelae is not clear. The aim of this study was to investigate the effects of PR on COVID-19 sequelae. A 52-year-old patient was hospitalized for 8 days, and the complaints of fatigue and dyspnea continued after being discharged. For this reason, an exercise program was recommended. The patient underwent a 6-week PR that consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Most studies on the effect of exercise on functional capacity and pulmonary function after discharge from COVID-19 hospital are currently limited to observational studies [21]. However, the results of previous studies showed that exercise therapy in COVID-19 survivors had a significant effect on functional capacity, especially 6-minute walking distance [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and pulmonary function [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on the effect of exercise on functional capacity and pulmonary function after discharge from COVID-19 hospital are currently limited to observational studies [21]. However, the results of previous studies showed that exercise therapy in COVID-19 survivors had a significant effect on functional capacity, especially 6-minute walking distance [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and pulmonary function [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Data were analyzed using SPSS software v. 22. The Shapiro-Wilk and Levene's tests were employed to evaluate the normality of the distribution of scores and homogeneity of variance among groups (P>0.05).…”
Section: Exercise Programmentioning
confidence: 99%